A List of Successes That Can Change the World: Essays Dedicated to Philip Wadler on the Occasion of His 60th Birthday - Lindley, Sam; McBride, Conor; Trinder, Phil; Sannella, Don (Lecture Notes in Computer Science, 2016)
This volume is published in Honor of PhilipWadler on the occasion of his 60th birthday, and the collection of papers forma Festschrift for him. The contributions are made by some of the many who knowPhil and have been influenced by him. The research papers included hererepresent some of the areas in which Phil has been active, and the editorsthank their colleagues for agreeing to contribute to this Festschrift. We attemptto summarize Phil Wadler's scientific achievements. In addition, we describethe personal style and enthusiasm that Phil has brought to the subject.